Double Down-Conversion and induced coherence - Mondino, Luigi; Alonso, Vidal (Ciencia)
The behaviour of the entangled two-particle system arising from down-conversion is analyzed semiclassically in terms of the induced coherence and the conditional state. The result is tested with the help of two fundamental interferometry experiments involving the frustrated pair creation, one of them with quantum markers and with erasers insertable in a delayed-choice mode. The capability of the conditional pilot wave of influencing the particle emission is discussed.